2012
DOI: 10.1089/scd.2011.0634
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Human Progenitor Cell Transplantation Optimizes Islet Regeneration Through Secretion of Paracrine Factors

Abstract: Transplanted human bone marrow (BM) and umbilical cord blood (UCB) progenitor cells activate islet-regenerative or revascularization programs depending on the progenitor subtypes administered. Using purification of multiple progenitor subtypes based on a conserved stem cell function, high aldehyde dehydrogenase (ALDH) activity (ALDH(hi)), we have recently shown that transplantation of BM-derived ALDH(hi) progenitors improved systemic hyperglycemia and augmented insulin secretion by increasing islet-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 49 publications
2
49
0
1
Order By: Relevance
“…Although the engraftment of human cells within ischemic muscle was infrequent, UCB ALDH hi cells were specifically recruited to the ischemic limb within 3 days of transplantation and stimulated the recovery of blood vessel and capillary density. Furthermore, ALDH hi cells function within the pancreas to promote islet revascularization after transplantation into streptozotocin-treated mice [45,46]. Collectively, these data suggest that UCB ALDH hi progenitor cells represent a readily available population of proangiogenic cells for the development of cellular therapies to promote endogenous revascularization.…”
Section: Discussionmentioning
confidence: 83%
“…Although the engraftment of human cells within ischemic muscle was infrequent, UCB ALDH hi cells were specifically recruited to the ischemic limb within 3 days of transplantation and stimulated the recovery of blood vessel and capillary density. Furthermore, ALDH hi cells function within the pancreas to promote islet revascularization after transplantation into streptozotocin-treated mice [45,46]. Collectively, these data suggest that UCB ALDH hi progenitor cells represent a readily available population of proangiogenic cells for the development of cellular therapies to promote endogenous revascularization.…”
Section: Discussionmentioning
confidence: 83%
“…There was a significant reduction in blood glucose AUC for MSC R vs MSC NR samples (Fig. 1b) [14,15]. Cell surface phenotype showed that both MSC R and MSC NR expressed the stromal markers CD90 and CD105 (>95%) without expression of the pan-leucocyte marker CD45 (data not shown).…”
Section: Resultsmentioning
confidence: 91%
“…In contrast, transplanted MSCs initiated endogenous islet recovery via paracrine stimulation [13]. In a series of publications, we have shown that human BM-derived MSCs stimulated the emergence of small, recipient-derived islet-like structures associated with the ductal epithelial niche within 7 days of injection into streptozotocin (STZ)-treated hyperglycaemic NOD/SCID mice [14,15]. Unfortunately, MSC samples showed donordependent variability in the capacity to improve glycaemia and prolonged expansion ex vivo reduced islet regenerative prowess [14].…”
Section: Introductionmentioning
confidence: 99%
“…This research group also showed that, at only 14 days after MSC transplantation, the blood glucose level decreased to lower than 200 mg/dl; and, after 28 days, it was reduced to that of normal mice (< 126 mg/dl). The transplantation of MSCs also simultaneously increased the number of IPCs and the insulin level in the blood (Bell et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…This positive paracrine effect on the damaged beta cells could help to protect these cells from apoptosis and to promote the proliferation of intrinsic pancreatic progenitor cells. This effect is also related to angiogenesis, cell protection, anti-inflammatory activities, promotion of mitosis, and apoptosis resistance (Bell et al, 2012;Gao et al, 2014;Xu et al, 2008). Furthermore, MSCs can trans-differentiate into insulin-producing cells (IPCs) in vivo in a suitable microenvironment (Chang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%